EFFICIENCY OF USING A SOLAR CONCENTRATOR FOR BIOMASS HELIOPYROLYSIS - Almardanov , Hamidilla Abdiganievich (Educational Research in Universal Sciences, 2023)
The article analyzes the efficiency of the solar concentrator for biomass heliopyrolysis and the saving of heat energy used for the specific needs of the device, as well as the thermal technical indicators of the device. The article also proposes a heliopyrolysis system with a solar concentrator to provide heat to the pyrolysis reactor. A temperature of 400-700 ℃ can be obtained as a result of the application of a solar concentrator to this type of pyrolysis device. As a result, it allows to reduce private energy consumption for the pyrolysis process by 30-35%. In this article, the goals of computational-theoretical research obtained in the process of heliopyrolysis are mainly directed to the approximate assessment of their thermal efficiency, taking into account the degree of optimization of thermal technical parameters.